Glutamine deprivation induces abortive s-phase rescued by deoxyribonucleotides in k-ras transformed fibroblasts. - Daniela Gaglio (Public Library of Science (PLoS), 2009)
Background Oncogene activation plays a role in metabolic reprogramming of cancer cells. We have previously shown that K-ras transformed fibroblasts have a stronger dependence on glycolysis and a reduced oxidative phosphorylation ability as compared to their normal counterparts. Another metabolic adaptation of cancer cells, that has long been established, is their propensity to exhibit increased glutamine consumption, although the effects induced by glutamine deprivation on cancer cells are still controversial. Methodology and principal findings Here, by using nutritional perturbations and molecular physiology, we show that reduction or complete depletion of glutamine availability in K-ras transformed fibroblasts causes a strong decrease of proliferation ability and a slower re-entry of synchronized cells into the cell cycle. The reduced proliferation is accompanied by sustained expression of cyclin D and E, abortive S phase entrance and is dependent on Ras signalling deregulation, since it is rescued by expression of a dominant negative guanine nucleotide exchange factor. The growth potential of transformed cells as well as the ability to execute the G(1) to S transition is restored by adding the four deoxyribonucleotides, indicating that the arrest of proliferation of K-ras transformed cells induced by glutamine depletion is largely due to a reduced supply of DNA in the presence of signalling pathways promoting G(1) to S transition. Conclusions and significance Our results suggest that the differential effects of glutamine and glucose on cell viability are not a property of the transformed phenotype per se, but rather depend on the specific pathway being activated in transformation. For instance, myc-overexpressing cells have been reported to die under glutamine depletion and not under glucose shortage, while the opposite holds for ras-transformed fibroblasts as shown in this paper. These different responses of transformed cells to nutritional stress should be taken into account when designing anti-cancer therapies that aim to exploit metabolic differences between normal and transformed cells.